Understanding the Functionality of Probiotics on the Edge of Artificial Intelligence (AI) Era - Asar, Remziye; Erenler, Sinem; Devecioglu, Dilara; Ispirli, Humeyra; Karbancioglu-Guler, Funda; Ozturk, Hale Inci; Dertli, Enes (MDPI, 2025)
This review focuses on the potential utilization of artificial intelligence (AI) tools to deepen our understanding of probiotics, their mode of action, and technological characteristics such as survival. To that end, this review provides an overview of the current knowledge on probiotics as well as next-generation probiotics. AI-aided omics technologies, including genomics, transcriptomics, and proteomics, offer new insights into the genetic and functional properties of probiotics. Furthermore, AI can be used to elucidate key probiotic activities such as microbiota modulation, metabolite production, and immune system interactions to enable an improved understanding of their health impacts. Additionally, AI technologies facilitate precision in identifying probiotic health impacts, including their role in gut health, anticancer activity, and antiaging effects. Beyond health applications, AI can expand the technological use of probiotics, optimizing storage survival and broadening biotechnological approaches. In this context, this review addresses how AI-driven approaches can be facilitated by strengthening the evaluation of probiotic characteristics, explaining their mechanisms of action, and enhancing their technological applications. Moreover, the potential of AI to enhance the precision of probiotic health impact assessments and optimize industrial applications is highlighted, concluding with future perspectives on the transformative role of AI in probiotic research.
Keywords: omics technologies; biotechnological optimization; AI-driven probiotic research; precision health; microbiota modulation; metabolite production; viability; HEALTH-BENEFITS; GUT MICROBIOME; UNLOCKING; PROTEINS; SURVIVAL; BACTERIA; SYSTEM; Biotechnology & Applied Microbiology; Food Science & Technology